Real-time and immediate effects of backward walking exercise on pain intensity and lumbopelvic movement control in individuals with chronic non-specific low back pain with lumbar flexion syndrome - Chan, Ellen; Chan, Lok-Yi; Fong, Hung-Kit; Mak, Yiu-To; Kwong, Patrick Wai-Hang; Sun, Eliza Rui; Yu, Clare C. W.; Tsang, Sharon M. H. (PLOS ONE, 2025)
Objective Backward walking may promote the preferential recruitment of lumbar extensors to optimize flexed spinal posture adopted LBP flexion subgroup. This cross-sectional study investigated the backward-walking exercise on a) real-time muscle activation, and b) its immediate effect on back pain intensity, movement control and lumbopelvic muscle activation in individuals with chronic non-specific LBP characterized with lumbar flexion syndrome. Method Thirty adults with chronic non-specific LBP with clinical manifestation of flexion syndrome received assessments of their movement control at static standing and during the five-minute forward walking test, conducted before and after a 15-minute treadmill walking training in forward or backward direction (as the immediate effect), while real-time adaptation of the lumbopelvic muscles during walking training was also evaluated. Comparisons of back pain intensity, ratio of the normalized electromyography (EMG) of the paired lumbopelvic muscles during walking, and performance of the lumbar movement control tests (LMC) using inferential statistics to analyze between- and within-subject effects differences for the a) real-time and b) immediate effects of the single session of walking training designated in a backward direction as compared to forward direction. Results Two-way repeated measures analysis of covariance (ANCOVA) was adopted to minimize the confounding effect from covariates identified (maximal tolerable gait speed for EMG amplitude analysis, and gender for pain intensity and performance in lumbar movement control (LMC) tests). Significant post-training improvement in pain intensity (p = 0.014) and overall performance of the LMC tests (p = 0.006) were found for those who received backward walking training. Significant overall between-group effect (p = 0.022–0.026) and time-and-group interaction effect (p = 0.004–0.022) of ipsilateral internal oblique (IO) to multifidus (MF) ratio were found in swing phases of both legs. For ipsilateral erector spinae (ES) to rectus abdominis (RA) ratio, significant time effect (p = 0.022), between-group differences (p = 0.031), and real-time reduction during forward walking in left swing phase, and significant between-group differences (p = 0.024), time-and-group interaction effect (p = 0.009), and real-time increase during backward walking in right swing phase were noted. Real-time increasing trend during backward walking and real time decreasing trend of ipsilateral MF to ES ratio during forward walking were observed in stance phase of both legs, with time-and-group interaction effect at 6th (p = 0.007) and 12th minute (p = 0.006) during walking training in left stance phase. Conclusions Backward walking exercise emerges to benefit LBP patients with lumbar flexion syndrome by inducing real-time increase in back extensors and deep stabilizing muscle recruitment together with the immediate post-training improvement in pain intensity and LMC test performance. Further research with longer training duration and larger sample size are recommended to better understand if greater and more sustainable therapeutic effect can be achieved with the walking exercise in backward direction for this specified LBP subgroup.